Poor Compliance with Sepsis Guidelines in a Tertiary Care Children's Hospital Emergency Room - Benjamin Louis Moresco; Benjamin Louis Moresco; Clinton Woosley; Clinton Woosley; Morris Sauter; Utpal Bhalala; Utpal Bhalala (Frontiers Media S.A., 2018)
ObjectivesThis study aimed to assess factors related to adherence to the Pediatric Advanced Life Support guidelines for severe sepsis and septic shock in an emergency room (ER) of a tertiary care children's hospital.MethodsThis was a retrospective, observational study of children (0-18 years old) in The Children's Hospital of San Antonio ER over 1 year with the International Consensus Definition Codes, version-9 (ICD-9) diagnostic codes for "severe sepsis" and "shocks." Patients in the adherent group were those who met all three elements of adherence: (1) rapid vascular access with at most one IV attempt before seeking alternate access (unless already in place), (2) fluids administered within 15 min from sepsis recognition, and (3) antibiotic administration started within 1 h of sepsis recognition. Comparisons between groups with and without sepsis guideline adherence were performed using Student's t-test (the measurements expressed as median values). The proportions were compared using chi-square test. p-Value ≤0.05 was considered significant.ResultsA total of 43 patients who visited the ER from July 2014 to July 2015 had clinically proven severe sepsis or SS ICD-9 codes. The median age was 5 years. The median triage time, times from triage to vascular access, fluid administration and antibiotic administration were 26, 48.5, 76, and 135 min, respectively. Adherence to vascular access, fluid, and antibiotic administration guidelines was 21, 26, and 34%, respectively. Appropriate fluid bolus (20 ml/kg over 15-20 min) was only seen in 6% of patients in the non-adherent group versus 38% in the adherent group (p = 0.01). All of the patients in the non-adherent group used an infusion pump for fluid resuscitation. Hypotension and ≥3 organ dysfunction were more commonly observed in patients in adherent group as compared to patients in non-adherent group (38 vs. 14% p = 0.24; 63 vs. 23% p = 0.03).ConclusionOverall adherence to sepsis guidelines was low. The factors associated with non-adherence to sepsis guidelines were >1 attempt at vascular access, delay in antibiotic ordering, fluid administration using infusion pump, absence of hypotension, and absence of three or more organs in dysfunction at ER presentation.